2002
DOI: 10.1029/2002gl014745
|View full text |Cite
|
Sign up to set email alerts
|

Observable signatures of a convectively generated wave field over the tropics using Indian MST radar at Gadanki (13.5°N, 79.2°E)

Abstract: An experiment was conducted in the month of June 2000 to study the atmospheric dynamical behavior in the troposphere and lower stratosphere in the presence of a cloudy and moist background environment due to the onset of the summer monsoon over Indian peninsula. The cardinal objective was to observe the gravity wave signatures in the convective environment. We successfully monitored the development, maximizing and weakening of convective phenomena within a time span of 3–4 hours on 21–22 June 2000. The vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 12 publications
7
42
0
Order By: Relevance
“…Few references exist over the tropical ocean where convection is the major GW source (Beres et al, 2002). For instance, recent radar observations revealed the characteristics of highly convective zone in regard to induced GW in the UTLS in the vicinity of Bay of Bengal region and Indonesian region (Dhaka et al, 2002(Dhaka et al, , 2005. GW activity in the LS was recently explored with radiosondes in the tropical Pacific in November to December 2001 (Sato et al, 2003), above the South-East Indian Ocean at Cocos Islands (12 • S, 97 • E) between September 1992 and June 1998 (Vincent and Alexander, 2000) and above Darwin area in October to December 2001 (Tsuda et al, 2004 …”
Section: Introductionmentioning
confidence: 99%
“…Few references exist over the tropical ocean where convection is the major GW source (Beres et al, 2002). For instance, recent radar observations revealed the characteristics of highly convective zone in regard to induced GW in the UTLS in the vicinity of Bay of Bengal region and Indonesian region (Dhaka et al, 2002(Dhaka et al, , 2005. GW activity in the LS was recently explored with radiosondes in the tropical Pacific in November to December 2001 (Sato et al, 2003), above the South-East Indian Ocean at Cocos Islands (12 • S, 97 • E) between September 1992 and June 1998 (Vincent and Alexander, 2000) and above Darwin area in October to December 2001 (Tsuda et al, 2004 …”
Section: Introductionmentioning
confidence: 99%
“…Gravity wave studies have been carried out in the past using the Indian MST radar observations over this latitude (Dutta et al, 1999;Dhaka et al, 2001Dhaka et al, , 2002Reddy et al, 2005;Kumar, 2006Kumar, , 2007Ratnam et al, 2008). Most of these studies aimed to explore the frequency spectra of gravity waves during various atmospheric conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Tsuda et al (1994a) reported that in the equatorial region, gravity wave generation was typically associated with deep convection. Dhaka et al (2001Dhaka et al ( , 2002 showed gravity wave activity associated with convection over a tropical region by using Indian MST Radar. These waves have typically periods of a few tens of minutes.…”
Section: V Subba Reddy Et Al: Studies On Atmospheric Gravity Wavmentioning
confidence: 99%